2013
DOI: 10.1037/a0031251
|View full text |Cite
|
Sign up to set email alerts
|

Timing, extent, and type of child care and children’s behavioral functioning in kindergarten.

Abstract: Prior research has unearthed a link between early education and care (EEC) experiences and worse behavioral functioning for children, yet the research has not clearly delineated whether this link is due to early entry into care (timing), extensive hours of care (extent), or use of center-based care (type). Using a nationally representative sample of children followed from infancy through kindergarten (N ≈ 6,000), we assessed links between EEC timing, extent, and type, and children's kindergarten functioning. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
2
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 46 publications
4
35
2
3
Order By: Relevance
“…These results are consistent with prior studies from the USA6 7 32 33 and UK8 but in contrast with Norwegian studies that showed quantity of childcare during the first 4½ years of life had little influence on children's externalising behaviour 9 10. One possible explanation for the contradictory results from studies conducted in the USA, UK and Australia compared with Norway may relate to the high level of government investment in childcare,3 family-friendly policies including long-paid parental leave entitlements34 and generally higher quality childcare arrangements in Nordic countries 3 10…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with prior studies from the USA6 7 32 33 and UK8 but in contrast with Norwegian studies that showed quantity of childcare during the first 4½ years of life had little influence on children's externalising behaviour 9 10. One possible explanation for the contradictory results from studies conducted in the USA, UK and Australia compared with Norway may relate to the high level of government investment in childcare,3 family-friendly policies including long-paid parental leave entitlements34 and generally higher quality childcare arrangements in Nordic countries 3 10…”
Section: Discussionsupporting
confidence: 93%
“…Our study was unique in that we captured type of care for all arrangements experienced by children (not just primary arrangements), classifying type as informal (i.e., family, relative, child care home) and formal (i.e., center-based care). Our results mirrored those from other studies, as more formal care was associated with higher teacher ratings of negative behaviors and, conversely, lower teacher ratings of positive behaviors (Coley, Votruba-Drzal, Miller, & Koury, 2013). In connection with multiple arrangements, prior work has found that the combination of particular types of care has been associated with child outcomes, such as two center-based care arrangements associated with reading skills and a home-center arrangement combination associated with higher social competence (Gordon et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…This study found that increased hours in preschool were not associated with socioemotional or behavioral functioning. Although not necessarily in conflict with findings from other low‐income samples (e.g., Votruba‐Drzal, Coley, & Chase‐Lansdale, ; Votruba‐Drzal, Coley, Maldonado‐Carreño, Li‐Grining, & Chase‐Lansdale, ), these results do contradict consistent findings across more economically diverse samples linking increased time spent in preschool to increases in children's problem behaviors (e.g., Belsky et al, ; Coley, Votruba‐Drzal, Miller, & Koury, ; Loeb, Bridges, Bassok, Fuller, & Rumberger, ; NICHD Early Child Care Research Network, ). Thus, looking at findings from the broader literature on preschool and children's behavior, it is plausible that the dearth of associations between preschool dosage and behavior is attributable to the economic characteristics of the children in the samples.…”
Section: Dosage Resultscontrasting
confidence: 67%